IDENTITY AND WRITING SKILLS IN HIGHER EDUCATION: A CASE STUDY IN THE UNIVERSITY OF DA NANG - NGUYEN, TRINH (Universitas Islam Negeri (UIN) Mataram, 2024)
Teaching English writing to Vietnamese learners, non-native English speaker, who come from different geographical location and cultural backgrounds is completely challenging and time-consuming. It is not an overnight success but it requires restless efforts and attempts from both teachers and learners. Writing letter is absolutely crucial as it is seen as a social practice in daily communication. This article is of great value for theoretical and practical purpose in teaching English writing as second language. It’s worthy to raise the awareness of learners that the merits of teaching writing do not only lie on teaching grammar and vocabulary but introducing learners to convey messages to serve the primary purpose of communication in a social context in the real world and there is an emphasis on teaching writing and cognitive style as well as cultural and experiential models of English native speakers. The study reveals that translation “bilingual– their mother tongue” is the main source of difficulty in writing process. Teachers, therefore, should pass the concept of “root thought” and “choice of meaning” on to the learners to enable them to recognize the cognitive process of writing and the distinctive features between their first language and English. This study makes some great contribution to theoretical and empirical perspectives of teaching writing as second language acquisition.